KAJIAN EMISI COâ DENGAN PENDEKATAN FAKTOR EMISI (FE) PADA BENTUK PENGGUNAAN LAHAN PERMUKIMAN DI DAERAH PINGGIRAN KOTA - , Dian Hudawan Santosa ([Yogyakarta] : Universitas Gadjah Mada, 2012)
At this time the issue of climate change and global warming is becoming an interesting discussion by various groups. CO â emissions is suppose to be one factor that can provide a significant impact on the phenomenon. The research was carried out in the suburbs in the District of Mlati aimed to determine the emission factors from the domestic activities of households to calculate the emissions of CO â in the suburbs in the District of Mlati based forms of land use settlement, assess the condition of emissions of CO â in the suburbs in the District of Mlati based forms of settlement and land use projections to assess the value and trend changes in CO â emissions in 2020 and 2030, on the outskirts of town in the District of Mlati. This study uses a survey method with a stratified random sampling technique proportionally. Its application in the form of the distribution of questionnaires and interviews to 364 respondents in each family head of household in District of Mlati. The variables used are household domestic activities of cooking fuel, the amount of transportation fuels, the amount of electrical power used and waste generated. This study uses data analysis of primary and secondary data analysis. Analytical techniques used in the form of descriptive analysis, analysis of the graphics, and statistical analysis. Based on the characteristics of the District of Mlati emission factor value is divided into two, namely the value of emission factors for rural and urban areas. CO â emission factor values in the rural areas in the district is 169.05 tonCOâ /ha/year, while the value of emission factors for urban areas amounted to 234.75 tonCOâ/ha/year. In urban areas in the District of Mlati capable of generating potential of CO â emissions by 59% and 41% in rural areas. Trends in COâ emissions between the years 1991 - 2009 always showed an increase where the rate of change of land amounting to 0.79% or 10.58 acres per year. COâ emissions projections based on changes of land in 2020 amounting to 295,975.305 tonCOâ and CO emissions in 2030 increased to 317,338.344 tonCOâ.